2002
DOI: 10.1046/j.1365-3148.2002.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Tick‐borne diseases in transfusion medicine

Abstract: Ticks are effective vectors of viral, bacterial, rickettsial and parasitic diseases. Many of the tick-borne diseases (TBDs) are of significance to transfusion medicine, either because of the risks they pose to the blood supply or the necessity for blood products required in their treatment. The transmission of tick-borne pathogens via blood transfusion is of global concern. However, among transfusion medicine practitioners, experience with most of these microorganisms is limited. Transfusion transmission of TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 177 publications
(200 reference statements)
0
15
0
1
Order By: Relevance
“…1,5,7 Human infection occurs mostly by aerosols, through inhalation of spores coming from infected secretions. 5,6 Less frequently, there are cases of transmission by ingestion of unpasteurized milk or fresh cheese 8,9 and more rarely through blood transfusion, 1,10 vertical route 11,12 or by sexual transmission. 13 The main characteristic of acute Q fever is its clinical polymorphism, manifesting itself over a wide range of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,7 Human infection occurs mostly by aerosols, through inhalation of spores coming from infected secretions. 5,6 Less frequently, there are cases of transmission by ingestion of unpasteurized milk or fresh cheese 8,9 and more rarely through blood transfusion, 1,10 vertical route 11,12 or by sexual transmission. 13 The main characteristic of acute Q fever is its clinical polymorphism, manifesting itself over a wide range of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Tick-borne infections are responsible for many emerging pathogenic bacterial diseases that significantly impact the health of humans and other vertebrates (13,40). These include spirochete infections, such as those caused by the Lyme disease pathogen Borrelia burgdorferi, and rickettsial infections by the human monocytic ehrlichiosis agent, Ehrlichia chaffeensis, the human granulocytic anaplasmosis agent, Anaplasma phagocytophilum, and the bovine anaplasmosis agent, Anaplasma marginale (5,9,12,13,27).…”
mentioning
confidence: 99%
“…Autoimmune phenomena have also been found to be contributory factors for thrombocytopenia in tick borne illnesses. Wong et al used flow cytometry to demonstrate presence of anti-platelet antibodies in patients with human granulomatous ehrlichiosis (8,9). However, in the review of the literature to date, we have not found a report of babesiosis causing new onset ITP in an otherwise healthy individual.…”
Section: Discussionmentioning
confidence: 99%